Constraining the Age and Source Area of the Molveno landslide Deposits in the Brenta Group, Trentino Dolomites (Italy) - von Wartburg, Jonas; Ivy-Ochs, Susan; Aaron, Jordan; Martin, Silvana; Leith, Kerry; Rigo, Manuel; Vockenhuber, Christof; Campedel, Paolo; Viganò, Alfio (Frontiers in Earth Science, 2020)
Rock avalanches are low frequency natural hazards that can alter landscape morphology, and constraining the timing, volume and emplacement dynamics of pre-historic rock avalanches is crucial for understanding the hazards posed by these events. Here we perform cosmogenic nuclide dating, topographic reconstruction and runout modelling and of the Molveno rock avalanche, located north of Lake Garda in the Province of Trento, Italy. The unique morphology of the deposits, which features numerous large scarps and prominent lineaments, have previously led researchers to interpret the Molveno rock avalanche as being the result of multiple events. Our results show that the Molveno rock avalanche had a volume of approximately 600 Mm3, and failed from a prominent niche located on Monte Soran. 36Cl cosmogenic nuclide dating results shows that the deposits were emplaced as a single event approximately 4.8±0.5 ka, and suggests that the unique deposit morphology is due to the emplacement processes acting during and soon after failure. Numerical runout modelling shows that this morphology could have resulted from a combination of runup and extensional spreading of the debris along the complex valley floor topography. The ages we determined for this event are coincident with the nearby Marocca Principale rock avalanche (5.3±0.9 ka), which may suggest a common trigger. Our results have important implications for interpreting the morphology of rock avalanche deposits, and contribute to the evolving understanding of rock avalanche processes in the Alps.